2007
DOI: 10.1016/j.ijadhadh.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the sample preparation procedure and analysis of cyanoacrylate adhesives using capillary electrophoresis

Abstract: In this study, the trace acid profile of cyanoacrylate adhesives was studied using capillary electrophoresis. Liquid-liquid extraction was employed as the sample preparation step prior to separation by capillary electrophoresis. The solubility of the adhesives was investigated using various organic solvents, e.g. hexane and dichloromethane, and chloroform was determined to be the optimum solvent as it enabled the full dissolution of the adhesive. A comprehensive stability study was performed over a three-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Whitaker et al [124] reported investigations on the sample preparation needed for the analysis of cyanoacrylate adhesives by CE. Besides some inorganic anions, formic acid (in pure monomer only) and cyanoacetic acid could be identified in the crude and pure monomer as well as the distillation residue.…”
Section: Technical Products and Other Applicationsmentioning
confidence: 99%
“…Whitaker et al [124] reported investigations on the sample preparation needed for the analysis of cyanoacrylate adhesives by CE. Besides some inorganic anions, formic acid (in pure monomer only) and cyanoacetic acid could be identified in the crude and pure monomer as well as the distillation residue.…”
Section: Technical Products and Other Applicationsmentioning
confidence: 99%